Organization of field internsip in grades of geography specialization - Варфоломєєва, Ірина (Pedagogy of Higher and Secondary Education, 2014)
Varfolomeyeva I. М. Organization of field internsip in grades of geography specialization. The article theoretically substantiates summer geography internship in the context of senior profession-oriented school aswell as methodical recommendations concerning improvement and put into practice theoretical bases of its organization in the 10th grade of geography specialization.